Third parties, outsiders, and renegades modern challenges to the two-party system in presidential elections - Smith, Melissa M., 1963- (Lexington studies in political communication., 2022)
"Third Parties, Outsiders, and Renegades analyzes 10 third-party, outsider, or renegade presidential candidates and explores his or her impact on the political process. The future viability of outsider candidates is discussed in light of current political polarization and the legacy of Donald J. Trump, the first elected outsider president"--